Soil Microbiological Attributes Under Different Vegetation Covers - Cristiane Figueira da Silva; Ingryd Cardoso Estaky Cabral; Gabriel Coutinho Oliveira de Lemos; Isabella Silva Lopes; Matheus Corrêa de Oliveira; Luiz Alberto da Silva Rodrigues Pinto; Marcelo Antoniol Fontes; Eliane Maria Ribeiro da Silva; Marcos Gervasio Pereira (Floresta e Ambiente)
Abstract The aim of the study was to characterize the microbiological activity of the soil and its relationship with soil attributes in a toposequence under different vegetation covers at the UFRRJ Botanical Garden. Soil samples were collected from the surface layer of the shoulder, backslope and footslope. These show little variation in slope, but have different vegetation cover. The shoulder and footslope are covered by tree species from different botanical families, and the middle third by grasses. The tree species (shoulder) and the grasses (backslope) showed higher values of microbial biomass carbon, soil enzyme activity, sporulation and species richness of arbuscular mycorrhizal fungi. The correlations found suggest the effect of chemical and physical attributes, especially the lower levels of P and coarse sand, on the increase in these soil microbiological attributes. Greater deposition of glomalin-related soil protein was observed in areas with tree species, with correlations with pH and TOC.